Phytochemical Analysis of Cnidoscolus aconitifolius (Euphorbiaceae) leaf with Spectrometric Techniques. - Omotoso , Abayomi E; Olorunfemi, Eseyin O; Mikailu, Suleiman (Nigerian Journal of Pharmaceutical and Applied Science Research, 2014)
The plant Cnidoscolus aconitifolius (Euphorbiaceae) commonly known as ‘efo Iyana-Ipaja’ in South-West Nigeria is reported to possess a number of medicinal values. Phytochemical Analysis of the n-hexane, dichloromethane, and ethyl acetate leaf extracts of Cnidoscolus aconitifolius were performed by using UV-Vis, FTIR and GC-MS. The crude extracts were scanned in the wavelength ranging from 200-800nm by using UV-spectrophotometer, while FTIR was carried out from 4000 – 400cm-1 and their characteristic peaks detected. The GC-MS analysis was carried out using GC-MS Model-QP2010 plus spectrophotometer. The compound detection employed the NIST Ver. 2.0-Year 2005 library. The UV-Vis profile showed different peaks ranging from 400 – 700nm with different absorption respectively. The FTIR spectrum confirmed the presence of alkanes, alkenes, alkynes, alcohols, aldehydes, ketones, carboxylic acids, esters and aromatics. The Phytochemical Analysis of the Cnidoscolus aconitifolius leaf extracts revealed 20 phyto-chemotypes with different therapeutic activities, among them, 9-Octadecenoic acid (Z) and its esters, n-Hexadecanoic acid, n-Octadecanoic acid, n-Octacosane, 1,2,3-Propanetriol and its derivatives, and l-(+)-Ascorbic acid-2,6-dihexadecanoate, were found to be present in major amount. The presence of some of these phyto-constituents in the plant provides the scientific basis for the therapeutic properties of the plant and thus recommended use as a plant of phyto-pharmaceutical importance.